The effect of voids on boundary migration during recrystallization in additive manufactured samples—a phase field study. (June 2022) - Zhang, Chunlei; Yadav, Vishal; Moelans, Nele; Juul Jensen, Dorte; Yu, Tianbo
Abstract: Experimental results show that voids inside additive manufactured (i.e. 3D printed) materials are unavoidable. As such samples are often post-printing annealed, it is thus of interest to understand how voids affect boundary migration. In this work, phase field simulations of recrystallization are carried out for systems containing voids and typical inhomogeneous microstructures. The simulation results show that the voids significantly affect the shape of the boundary and its migration kinetics during recrystallization. The location of the voids in relation to the inhomogeneous deformation microstructure is furthermore found to affect local boundary migration. The results are not only of importance for optimizing annealing of printed samples, but also for understanding local boundary migration in particle containing alloys. Graphical abstract: Image, graphical abstract